Research Gaps in Radio Frequency Identification Technology Implementation in Warehouses - Haswika, Haswika; Qurtubi, Qurtubi; Setiawan, Danang; Supriyadi, Supriyadi (Bright Publisher, 2024)
Warehouses are important in enabling and supporting the efficient execution of logistical activities. Integrating radio frequency identification (RFID) technology can catalyze innovation in warehouse operations by reducing the tracking and management of items. This study aims to identify novel research prospects for integrating RFID technology within warehouse operations. The researchers conducted a comprehensive literature evaluation by examining articles indexed by Scopus. This study has comprehensively analyzed the critical elements of each paper reviewed, including the research aims, findings, outputs, and gaps. These characteristics contribute to identifying innovative research directions in the context of RFID technology and its application in warehouse environments. This study provides a significant result, as no recent literature review on a similar topic exists. Furthermore, this literature review aims to address the existing theoretical void by building upon prior research and offering scientific contributions by presenting a complete and comprehensive literature review.